Language hybridity as psychological resistance: Identity construction in native american literature from a social psychology perspective - Nie, Shijuan (Environment and Social Psychology, 2025)
This article examines the intricate ways through which language hybridity in Native American literature simultaneously substantiates and significantly expands Homi Bhabha’s theoretical model of cultural hybridity, demonstrating how strategic linguistic hybridization operates as a mechanism for cultural resistance, preservation, and regeneration. Through comprehensive textual analysis of Louise Erdrich’s "Love Medicine," N. Scott Momaday’s "House Made of Dawn," and Leslie Marmon Silko’s "Ceremony," the study illuminates how Native American authors’ deliberate integration of tribal languages within English narratives constructs politically transformative spaces that transcend Bhabha’s conceptualization of the ’third space,’ functioning not merely as contact zones but as dynamic sites for generating, sustaining, and cultivating emergent cultural formations. Employing three analytical frameworks—language hybridity as cultural survival mechanism, cultural negotiation as identity construction strategy, and linguistic spatiality as pathway for cultural rejuvenation and psychological healing—this investigation reveals how Native American literature fundamentally reconceptualizes hybrid zones as simultaneous repositories of traditional knowledge systems and generative spaces for cultural innovation. By integrating social psychological frameworks including Berry’s acculturation model, Tajfel and Turner’s social identity theory, and recent developments in linguistic anthropology, the study contributes to postcolonial theory by demonstrating how marginalized communities strategically employ hybrid linguistic spaces not only for cultural continuity but as active instruments of psychological resilience and collective empowerment in contemporary contexts.